(untitled) (Journal of Economic Research & Business Administration, 2016)
Funding issues and involvement in the educational system of funds from different sources are some of the key issues in higher education, which is increasingly becoming a major sector of the economy both in terms of resource consumption, and in terms of the contribution to economic and social progress. Forming area management system of higher education at a level consistent with international standards, and in particular the development of the financing system under the requirements of the world community, of course, provides a solution to the many problems existing in this sphere. In this regard, the financing problems of the sector must be considered not only at the level of the university, improving the financing system should become an important part of organizational activities of higher education, at the level of the state. All these activities should be aimed at increasing the competitiveness of national universities, which are becoming increasingly active market participants.